Model of Acceptance of E-Health Services - Mohammad Taghi Taghavifard; Payam Hanafizadeh; Jahanyar Bamdad-Soofi; Akbar Yoosefvand (Hamadan University of Medical Sciences, 2020)
Aims: Understanding the factors that underpin the adoption of new healthcare electronic systems and services is of great importance. Therefore, the aim of the present study was to provide the model of acceptance of electronic health services by patients. Instruments & Methods: This descriptive-correlational study was conducted on 357 patients in Tehran hospitals during 2018-2019. The subjects were selected by convenience sampling method and completed a questionnaire including demographic information and the main model structural components (audience, cerebral process, and conduit). SPSS 22 software was used for descriptive analysis of data and partial least squares method and Smart PLS 3.2.8 software were used to verify the conceptual model. Findings: The influence of factors related to receiver of health services or audience (t=9.955), factors related to cerebral process (t=5.206) and also, factors related to conduit (t=3.350) were significant on acceptance of e-health services (p<0.05). Therefore, all relationships between model variables were confirmed. Conclusion: The provided model of acceptance of e-health services is confirmed and based on this, one can predict the effective factors in determining the acceptance of e-health services.